Trusting the Police: Comparisons across Eastern and Western Europe - Staubli, Silvia (Kultur und soziale Praxis, 2017)
The police can be seen as a governmental institution or as an organizational body, where especially the work - effectiveness, or fairness in encounters - is valued. Through the combination of these approaches and the inclusion of social trust and criminal victimization, Silvia Staubli offers an understanding beyond existing literature on institutional trust and procedural fairness. Moreover, due to analyses for Eastern and Western Europe, she addresses experts from sociology, political science, criminology, and social anthropology equally. Beyond, the study offers an insight to the public on how public opinions towards institutions are shaped.